MARKETING STRATEGIES TO USE IN THE CAFETERIA OF THE CITY OF RIOBAMBA - Vallejo Sánchez, Diego Patricio; Atiencia Aucancela, Estefanía Lissette; Slusarczyk Antosz, Maria (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
This article aims to identify the marketing strategies to use in coffee shops in the city of Riobamba that affect in a timely manner with respect to their sales, there are about 149 coffee shops already registered in the municipality, although it was also identified that its activities Perform based on experience. Within the aforementioned project we present an exploratory type investigation for having made a diagnosis; It also has a descriptive level because primary and secondary historical information was taken to gather fundamental characteristics of the research, as well as using a qualitative approach and a quantitative approach, applying techniques such as the survey, in order to identify the way of attracting customers. Of the 100%, 55% mentioned that the only strategy they put into practice are social networks, information extracted from the owners of each of the coffee shops, it can be concluded that most of them have stability in coffee shops that have a quite ample time already in the market and continue to grow despite not using other strategies for more influx of customers and obtaining more revenue.